Acute health effects from exposure to indoor ultrafine particles—A randomized controlled crossover study among young mild asthmatics. (7th July 2021) - Laursen, Karin Rosenkilde; Rasmussen, Berit Brøndum; Rosati, Bernadette; Gutzke, Vibeke Heitmann; Østergaard, Kirsten; Ravn, Peter; Kjærgaard, Søren Kenneth; Bilde, Merete; Glasius, Marianne; Sigsgaard, Torben
Abstract: Particulate matter is linked to adverse health effects, however, little is known about health effects of particles emitted from typical indoor sources. We examined acute health effects of short‐term exposure to emissions from cooking and candles among asthmatics. In a randomized controlled double‐blinded crossover study, 36 young non‐smoking asthmatics attended three exposure sessions lasting 5 h: (a) air mixed with emissions from cooking (fine particle mass concentration): (PM2.5 : 96.1 μg/m 3 ), (b) air mixed with emissions from candles (PM2.5 : 89.8 μg/m 3 ), and c) clean filtered air (PM2.5 : 5.8 μg/m 3 ). Health effects (spirometry, fractional exhaled Nitric Oxide [FeNO], nasal volume and self‐reported symptoms) were evaluated before exposure start, then 5 and 24 h after. During exposures volatile organic compounds (VOCs), particle size distributions, number concentrations and optical properties were measured. Generally, no statistically significant changes were observed in spirometry, FeNO, or nasal volume comparing cooking and candle exposures to clean air. In males, nasal volume and FeNO decreased after exposure to cooking and candles, respectively. Participants reported additional and more pronounced symptoms during exposure to cooking and candles compared to clean air. The results indicate that emissions from cooking and candles exert mild inflammation in asthmatic males and decrease comfort among asthmatic males and females.